PENGEMBANGAN PERANGKAT UNTUK PEMBELAJARAN FLIPPED CLASSROOM BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN EKONOMI - Lilis, Bernadeta; Achmadi, Achmadi; Basri, Muhammad (STKIP Persada Khatulistiwa Sintang, 2023)
Learning success may be impacted by educational technology. Teachers must transition from verbalist orators to those with the capacity to foster an environment that is conducive to learning. The objective of this research is to create resources for flipped classroom instruction in the Class X Economics course at SMA Negeri 1 Kayan Hulu. The method used is research and development. The development model used is ADDIE (Analyze, Design, Develop, Implement, and Evaluate). The research participants consisted of 2 expert validators, 2 teachers as assistants and 35 class X students of SMA Negeri 1 Kayan Hulu. This research was conducted at SMA Negeri 1 Kayan Hulu, Sintang District, West Kalimantan. The instruments used are Assessment Questionnaires, Student Response Questionnaires, Observation Sheets and Tests. Data analysis techniques include validity analysis, practicality analysis and effectiveness analysis. The conclusion of this study is that the learning tools are arranged according to the independent curriculum, namely teaching modules, learning videos, and student worksheets. The results of the validation of the developed device are categorized as good and suitable for use. Judging from the percentage of student learning completeness, an average of 85.75 is obtained and the percentage of classical completeness is 100%.